2020
DOI: 10.1289/ehp7133
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ambient Air Pollution Exposures and Brain Imaging Markers in Korean Adults: The Environmental Pollution-Induced Neurological EFfects (EPINEF) Study

Abstract: BACKGROUND: Only a limited number of neuroimaging studies have explored the effects of ambient air pollution in adults. The prior studies have investigated only cortical volume, and they have reported mixed findings, particularly for gray matter. Furthermore, the association between nitrogen dioxide (NO 2) and neuroimaging markers has been little studied in adults. OBJECTIVES: We investigated the association between long-term exposure to air pollutants (NO 2 , particulate matter (PM) with aerodynamic diameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 51 publications
(71 reference statements)
2
25
0
Order By: Relevance
“…Healthy subjects were participants of the Environmental Pollution‐Induced Neurological EFfects (EPINEF) study, which is based on community. Through local advertisements, individuals without known neurological diseases (e.g., any kind of dementia, movement disorders, or stroke) were recruited and enrolled in this cohort (Cho et al, 2020). The 96 participants in the healthy group did not have subjective memory complaints and objective cognitive decline.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy subjects were participants of the Environmental Pollution‐Induced Neurological EFfects (EPINEF) study, which is based on community. Through local advertisements, individuals without known neurological diseases (e.g., any kind of dementia, movement disorders, or stroke) were recruited and enrolled in this cohort (Cho et al, 2020). The 96 participants in the healthy group did not have subjective memory complaints and objective cognitive decline.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, traffic-related pollution may contain elements characterized by neurotoxic effects, especially heavy metals such as lead, cadmium, mercury, and selenium already associated with ALS risk [61][62][63][64][65][66]. A neuroimaging study showed that long-term exposure to high ambient air pollution may lead to cortical thinning and reduced subcortical volume in adults [67].…”
Section: Discussionmentioning
confidence: 99%
“…69 Imaging evidence of an association between PM2.5 exposure and neurodegenerative changes is provided by longitudinal studies of healthy patients with interval MRI scans, which have shown white matter loss in those exposed to greater concentrations of PM2.5. [70][71][72][73][74] PM(coarse) has been less well-studied and only a single report linking exposure in women to decreased mini-mental status examination (MMSE) score has been published. 75 Exposure to PM10, particularly in patients harboring the APOE4 allele, has been shown to associate both with dementia incidence and rate of cognitive decline, as well as front-temporal thinning on MRI.…”
Section: Dementiamentioning
confidence: 99%
“…75 Exposure to PM10, particularly in patients harboring the APOE4 allele, has been shown to associate both with dementia incidence and rate of cognitive decline, as well as front-temporal thinning on MRI. 66,74,[76][77][78] The effects of exposure to ground-level ozone (O3) remain less clear, as there have not been as strong associations with dementia incidence 76 , increased odds of amyloid PET positivity 68 , or MMSE score decline. 66 Nitrogenous gases have shown an association with vascular dementia 79 , global brain atrophy 74 , and a slightly faster rate of decline in those with the APOE4 allele, with differing results for MMSE-scored cognitive decline and all-cause dementia.…”
Section: Dementiamentioning
confidence: 99%
See 1 more Smart Citation